Debris Flow Induced by Heavy Rainfall in Hulu Terengganu: Hydrological and Geological Analysis - Ahmad S.A.; Samad D.H.; Yusof N.M.; Sidek L.M.; Basri H.; Omar S.M.A.; Ahmad F.; Muda Z.C.; Hafez Ahmed M.A. (Springer Science and Business Media Deutschland GmbH, 2024)
Terengganu is one of the states in Malaysia that will be the most affected by the northeast monsoon which usually happens early in November and lasts until March every year. Continuous heavy rainfall may cause various natural disasters including debris flow. Due to the features of sudden outbursts and high energy density, debris flow has caused a significant number of deaths in several geohazard incidents in Malaysia. In contrast to other types of landslides, almost all debris flows begin on natural topography. The majority of the incident was caused by rain. Intense and severe rainfall raises the water content and pore water pressure inside the remaining soil, potentially causing landslides. Based on a recent event on February 27, 2022, this study will examine the hydrological analysis including rainfall time series and rainfall distribution by using rainfall data from February 23, 2022, until March 1, 2022, along with geological analysis of the upper part of Hulu Terengganu. As a result, heavy and sustained rainfall has proved to become the primary cause of debris flow. The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2023.